Trends of Hospital Care Services During COVID-19 Pandemic in a Tertiary Care Hospital at Province 5 - Lamichhane, Basant (Med Phoenix, 2021)
Introduction: Health systems all around the globe have greatly been affected by the increasing demand for care of people with COVID-19. A well-prepared health system should have the capacity to maintain equitable essential health services in any pandemic or emergency. In this current scenario, this study aims to study the trends of hospital care services in one of the remote tertiary hospitals of province 5. The aim of the study was to assess the trends of various important health services along with the onset of the COVID-19 pandemic. Methods: A cross-sectional study was conducted in which data of the number of OPD cases, emergency cases, inpatients, deliveries, number of surgeries (major and minor), and the number of USG services were collected. Data of seven months prior to the onset of pandemic (August 15th, 2019 to March 15th, 2020) were compared with data of seven months following the onset of the pandemic (March 16th to October 16th, 2020) were recorded, compared, and plotted. Results: In regard to inpatients, there was an increment of 47.57%, the number of emergency cases increment by 41.90%, and the number of delivery increments by 94.70% was detected compared to seven months’ data prior to the onset of the pandemic. On the other hand, a reduction in total OPD, total number of surgeries, and USG by 32.7 %, 13.04%, 5.26 % respectively were detected. Looking through the trend, there was a decline in the number of OPD visits, inpatient cases, and emergency cases initially for three months (March-May) following the onset of the pandemic but along with an upsurge of the COVID pandemic, there was a marked increase in these services. Conclusions: The depiction of such trends of seeking and use of health services in resource-limited tertiary centers during this pandemic reflects the need of strengthening the overall health system. It also emphasizes the importance of the need of addressing non-COVID services during a pandemic, which was greatly affected by COVID-19.